(untitled) (Food In, 2012)
Scombroid syndrome - histamine poisoning is one of the most common form of intoxication caused by seafood consumption. The poisoning incidents are often underestimated due to mild or not-recognized symptoms, making difficult to attribute the responsibility for the outbreak and to improve proper hygienic practices. To help our students in a pragmatic and scientific approach, this article contains: definition and generalities on histamine poisoning; histamine and other biogenic amines formation; symptoms in humans; how to prevent scombroid syndrome; mandatory rules and official sampling in the European Union; biogenic amines as freshness indices; seafood associated in scombroid syndrome; foods, other than seafood, responsible of scombroid syndrome or with high levels of biogenic amines; detection of histamine and other biogenic amines in foods. The article is completed by the enclosure of an illustrated guide to the identification of fish species marketed in Italy most involved in scombroid syndrome (edited by Cristian Bernardi).